Tradisi Penarikan Barang Seserahan dalam Perkawinan Pasca perceraian Perspektif ‘Urf di Desa Lenteng Sumenep Madura - Haiza Nadia (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2022)
(The tradition of handing over household furniture is already familiar because most people in Sumenep Regency carry out this seserahan tradition in the form of handing over a number of household furniture in various ways, but the tradition of offerings that occurred in Lenteng Timur Village, Lenteng District, Sumenep Regency is after a husband and wife officially divorced, that is, some of the items that were handed over were asked to return after they were officially divorced and some were not asked to return even though they were divorced. This research belongs to the type of empirical research. This research is called field research or field research. This research is included in empirical research that examines relationships with society, namely in the form of the tradition of taking offerings in post-divorce marriages in Lenteng Timur Village, Lenteng District, Sumenep Regency. The approach used is a case study approach. In this study, the data analysis method used was qualitative data analysis. The results of this study indicate that in the process of implementing the withdrawal of the goods in this post-divorce marriage, after the two (husband and wife) have officially divorced, the people in Lenteng Timur Village, Lenteng District, Sumenep Regency carry out the process of withdrawing the surrendered goods, usually when a husband and wife are not blessed with children and the marriage only goes through the household which briefly. As for the items that were taken back by the ex-husband as a whole, without exception. The practice of withdrawing the items given by the husband due to a divorce that occurred in Lenteng Timur Village, Lenteng District, Sumenep Regency, when analyzed using ’urf, namely: ’Urf fasid, ’Urf ’amali, and â€˜Urf khas.)